2015
DOI: 10.1038/onc.2015.223
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Upregulation of long noncoding RNA ZEB1-AS1 promotes tumor metastasis and predicts poor prognosis in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related mortality worldwide. Despite progress in diagnostics and treatment of HCC, its prognosis remains poor. Emerging studies showed that long noncoding RNAs (lncRNAs) have crucial regulatory roles in cancer biology. In the current study, differentially expressed lncRNAs between HCC and paired non-tumor tissues were identified using microarrays. The effects of a specific differentially expressed lncRNA (termed ZEB1-AS1) on tumor progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
231
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(246 citation statements)
references
References 43 publications
15
231
0
Order By: Relevance
“…However, an increased level of ZEB2 in the cytosol was revealed to downregulate E-cadherin, and enable cells to undergo EMT (31). Similarly, ZEB1-AS1 upregulation has been reported to increase the promoter activity of the ZEB1 gene resulting in the repression of E-cadherin, and induction of EMT in hepatocellular carcinoma (22). The results of the present study identified a co-expression pattern in ZEB2 and ZEB2-AS1 in oral tumor samples.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…However, an increased level of ZEB2 in the cytosol was revealed to downregulate E-cadherin, and enable cells to undergo EMT (31). Similarly, ZEB1-AS1 upregulation has been reported to increase the promoter activity of the ZEB1 gene resulting in the repression of E-cadherin, and induction of EMT in hepatocellular carcinoma (22). The results of the present study identified a co-expression pattern in ZEB2 and ZEB2-AS1 in oral tumor samples.…”
Section: Discussionsupporting
confidence: 48%
“…The ZEB transcription factors may downregulate the expression of miR-200 family miRNAs. In addition, natural anti-sense transcript ZEB1-AS1 was demonstrated to enhance the transcription of ZEB1 and increase mRNA stability within the cytosol (30,22). Similarly, ZEB2 stability may also be enhanced by ZEB2-AS1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZEB2-AS1 is a recently identified lncRNA that has been demonstrated to perform significant functions in HCC (14,15). It is a non-coding antisense transcript from the promoters of ZEB2, which is reported to function as a transcription factor and is associated with a number of distinct types of cancer (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger E-box-binding homeobox 2 antisense RNA 1 (ZEB2-AS1) is a non-coding oncogene identified in human hepatocellular carcinoma (HCC) (14). Li et al (15) demonstrated that the relative transcript level of ZEB2-AS1 was upregulated in HCC in vivo and in vitro and functioned as a prognostic factor for HCC pathogenesis.…”
Section: Introductionmentioning
confidence: 99%